2016
DOI: 10.1002/pc.24127
|View full text |Cite
|
Sign up to set email alerts
|

Rheological, Mechanical, and thermal properties of polylactide/cellulose nanofiber biocomposites

Abstract: Biocomposites based on polylactide (PLA) and cellulose nanofibers (CNFs) were prepared via a solution method. The effects of CNFs on rheological, mechanical, thermal, and optical properties of PLA were investigated. Scanning electron microscopy showed that the CNFs were fairly dispersed/distributed in the PLA. Significant increases in the rheological properties of PLA/CNF composites and a remarkable shear-thinning behavior were observed. Also, apparent yield stress and a transition from liquid-to solid-like be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 40 publications
(102 reference statements)
3
17
0
Order By: Relevance
“…However, for the samples based on the solution-prepared PLA-CNC masterbatch, a shear-thinning behavior for g à without any plateau region at low frequencies is observed and G 0 values tend towards a plateau at low frequencies, illustrating clearly the strong effect of CNCs on the rheological properties of PLA/ CNC composites. This is an indication of a network formation and a transition from liquid-to solid-like behavior as observed for polymer-cellulose composites and nanocomposites [5,9,10,16,17]. We attribute this behavior to the good dispersion of the CNCs in the samples prepared with the PLA-CNC masterbatch.…”
Section: Rheologysupporting
confidence: 58%
“…However, for the samples based on the solution-prepared PLA-CNC masterbatch, a shear-thinning behavior for g à without any plateau region at low frequencies is observed and G 0 values tend towards a plateau at low frequencies, illustrating clearly the strong effect of CNCs on the rheological properties of PLA/ CNC composites. This is an indication of a network formation and a transition from liquid-to solid-like behavior as observed for polymer-cellulose composites and nanocomposites [5,9,10,16,17]. We attribute this behavior to the good dispersion of the CNCs in the samples prepared with the PLA-CNC masterbatch.…”
Section: Rheologysupporting
confidence: 58%
“…The findings revealed that reinforcing by 1 wt.% CNF could increase both the tensile strength and Young's modulus by 17%. Similarly, Safdari et al [54] also reported that the tensile strength and Young's modulus of PLA/5 wt.% CNF were higher by 31 and 50%, respectively, compared to the neat PLA. Besides that, CNF had a large specific surface area due to its small size and was found to be a heterogeneous nucleation site for crystallization in PLA.…”
Section: Mechanical Performancementioning
confidence: 81%
“…[26][27][28] Furthermore, CNCs are expected to provide favorable structural orientation and rheological and mechanical properties during the printing process. [29][30][31] CNCs containing inks usually exhibit shear thinning behavior even without the addition of any rheology modifiers, where CNCs are oriented preferably in the printing direction. 12,24 CNCs with carboxyl functional groups (charge density 0.5 mmol g −1 ) useful for crosslinking 14 and with proven cytocompatibility (cell growth after 15 days of incubation) 14,32 were used in the current study for the fabrication of biomedical hydrogel scaffolds.…”
Section: Introductionmentioning
confidence: 99%